2021
DOI: 10.3390/cancers13164208
|View full text |Cite
|
Sign up to set email alerts
|

Microdissected Tissue vs Tissue Slices—A Comparative Study of Tumor Explant Models Cultured On-Chip and Off-Chip

Abstract: Predicting patient responses to anticancer drugs is a major challenge both at the drug development stage and during cancer treatment. Tumor explant culture platforms (TECPs) preserve the native tissue architecture and are well-suited for drug response assays. However, tissue longevity in these models is relatively low. Several methodologies have been developed to address this issue, although no study has compared their efficacy in a controlled fashion. We investigated the effect of two variables in TECPs, spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…In the future, the latter issue can be overcome by advances in live-imaging microscopy, a technique that allows a single tissue slice to be analyzed at multiple time points. Moreover, an adaptation to the cancer-on-chip approach could eventually reduce the amount of tumor material required for the analysis of tumor sensitivity, as well as create a more controllable environment to mimic in vivo pharmacokinetic conditions [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the future, the latter issue can be overcome by advances in live-imaging microscopy, a technique that allows a single tissue slice to be analyzed at multiple time points. Moreover, an adaptation to the cancer-on-chip approach could eventually reduce the amount of tumor material required for the analysis of tumor sensitivity, as well as create a more controllable environment to mimic in vivo pharmacokinetic conditions [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…They used 3 PDX-TS and found that rocking on a cell strainer (very similar to titanium grids rotating) in serum‐free aDMEM/F12 K medium with R1881 was optimal to preserve proliferation and prevent apoptosis. Proof of concept studies in PDX-TS have developed a method to examine many tissues at once in 96-well format by a method they call micro-dissected tissue (MDT) ( 14 , 15 ). MDT are 500 µm in diameter, compared to normal TS which are 3-5 mm, thus MDT permits more precise tissue acquisition and potentially many more experimental endpoints.…”
Section: Tissue Slice Culture Methodsmentioning
confidence: 99%
“…Dorrigiv et al. optimized this by using cell line xenografts as the tissue source ( 15 ). They also developed a method to create an FFPE microarray from the MDT (MDTMA) ( 14 ).…”
Section: Tissue Slice Culture Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…135 Furthermore, ex vivo tumor samples maintain naturally-occurring tumor heterogeneity, as they contain both stroma and tumor cells, thereby retaining the complex interplay between these two cell types. 140–142…”
Section: Radiotherapy-compatible Microfluidic Devicesmentioning
confidence: 99%